DEVELOPING OF FLASH CARD MEDIA TO TEACH VOCABULARY SKILL ON DESCRIPTIVE TEXTS FOR VIII GRADE STUDENT OF MTS SYEKH SUBAKIR 2 SUMBERASRI - Nur Fadilah, Richo; Saifudin, Ahmad; Rofi'ah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the process of developing flashcard media for descriptive text learning and also to determine the results of developing flashcard media for teaching descriptive text in class VIII at MTs Syekh Subakir 2 Sumberasri, in accordance with the source of the problem that has been found, namely the ability to memorize English vocabulary which is still relatively low. This studyis a qualitative research, the technique used for data collection in this research is a simple saturation technique with a sample of 18 students, this research uses the ADDIE model development, this model was chosen because it is in accordance with the media development carried out by the researcher,The instruments used in this study were questionnaires from media experts, material experts and student response questionnaires. Based on the responses, the flashcard media development was quite effective, with expert validation showing a score of 90.0% from media experts and 83.5% from content experts. Meanwhile, the student response score was 66.8%. This indicates that flashcard learning media is suitable for use in learning.